Educating Future Physicians for a Minority Population: A French-language Stream at the University of Ottawa - Drouin, Jeanne; Jean, Pierre (Academic Medicine, 2002)
Abstract The Faculty of Medicine at the University of Ottawa has recently developed a French-language undergraduate medical education stream in order to train physicians for the francophone minority population of the province of Ontario. This new program was planned with the following societal requirements in mind: the need to receive health care in one's mother tongue, the need to have physicians who know the community, and the expectation of receiving good medical care in an ambulatory setting. A systematic educational planning model was used in order to develop three educational innovations in response to these needs and expectations: a communication skills laboratory; early student exposure to the ambulatory, primary care setting for development of clinical skills; and clerkship rotations in a francophone community hospital. Program developers provided ongoing faculty development activities in order to prepare francophone faculty for their new roles. They also considered student participation in program development an essential element of its success. The program has positive outcomes both within and outside the Faculty of Medicine. These include an enrichment effect on the English-language stream, an increased interest in medical education, student satisfaction with their community hospital clerkship rotations, and the recognition of the educational program as a national resource for francophone minority groups. Medical schools that serve minority population groups may benefit from the experience gained at the University of Ottawa.

La pratique de la physiothérapie en milieu minoritaire : mon expérience en tant que francophone à l’Hôpital de Hamilton - Goulet, Anik (Reflets, 2002)

Le rôle de l’hôpital communautaire Montfort comme pilier francophone de formation - Joanisse, Dr. John (Reflets, 2002)